2011
DOI: 10.1136/vr.c7432
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of botulism types C and D in cattle by a monoclonal antibody‐based sandwich ELISA

Abstract: This study was undertaken to evaluate two monoclonal antibody-based sandwich ELISAs (sELISAs) for the detection of Clostridium botulinum neurotoxins (BoNTs) types C and D from culture-enriched intestinal content samples from cattle. To validate the diagnostic significance of the presence of cultivable, toxin-producing C botulinum in the intestines of cattle, samples from both suspect and non-suspect botulism cases were examined. BoNT was detected by both sELISAs in a greater number of suspect animals than by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 14 publications
4
16
1
Order By: Relevance
“…3B-E, left panel). [46][47][48]79,80 An exception was the most recent ELISA described as multiplex approach to detect six BoNT serotypes including BoNT/C and DC which reached sensitivities similar to those of the ELISAs established in this work (LODs: 2.2 and 0.9 pg mL −1 for BoNT/C and DC, respectively). 3B-E (right panel) displays standard curves of three experiments for each of the four toxins, including a four-parametric curve fit.…”
Section: Establishing Sandwich Elisas For Specific Detection and Diffsupporting
confidence: 59%
“…3B-E, left panel). [46][47][48]79,80 An exception was the most recent ELISA described as multiplex approach to detect six BoNT serotypes including BoNT/C and DC which reached sensitivities similar to those of the ELISAs established in this work (LODs: 2.2 and 0.9 pg mL −1 for BoNT/C and DC, respectively). 3B-E (right panel) displays standard curves of three experiments for each of the four toxins, including a four-parametric curve fit.…”
Section: Establishing Sandwich Elisas For Specific Detection and Diffsupporting
confidence: 59%
“…In the present study, these results had showed some similarities observed as in under developing countries like rural area of Pakistan has not correct quality of drinking sources of water for domestic purposes. Same results derived as given by the study's results from Brooks et al (2011), it reported that in most of the developing countries, the quality of drinking water very not good as find some bacterial specious as per 100 ml of potable water used in domestic purpose. The recommend drinking water values of all limits under WHO guidelines is 100 ml per sample for detecting the total coliform group [15].…”
Section: Fig3: the Graph Shows The Different Dose Effect On Removingsupporting
confidence: 55%
“…C. Boulinum with Types A, B, E, and only F in rare cases found which cause illness in humans and animals. Especially C. Bolulinum with Types C and D cause illness in mammals and birds and type G are identified in 1970 which cause of infection in humans or animals [2]. The word of Botulism read from the language Latin as botulus, and its meanings is sausage.…”
mentioning
confidence: 99%
“…This observation parallels findings in other species. For example, researchers have observed a low occurrence of C. botulinum spores in intestinal samples from clinically normal cattle . In addition, isolation of C. botulinum from fecal or GI content samples from people is considered confirmatory evidence for botulism, because the organism is rarely encountered in specimens from humans in the absence of disease .…”
Section: Discussionmentioning
confidence: 99%